How season of birth affects Schizophrenia in Sri Lanka - Peramuna, P.D.O.S.D.; Fernando, L.H.; Wanigatunga, P.S.; Kulasiri, W.G.M.M.T.; Pathirage, C.L.; Prathapan, S.; Gambheera, H. (Proceedings of Proceedings of the Scientific Sessions 2016, FMS, USJP in collaboration with SJGH, 2016)
Attached

Objectives: To study any association between the development o f schizophrenia and the season in which the birth took place. M ethods: A descriptive cross sectional study was done on a sample o f 684 discharged patients from the National Institute o f Mental Health, who were treated for schizophrenia. Socio-demographic factors and other details were extracted from records. Each patient was contacted over the telephone to obtain his/her date and place o f birth. The date and place of birth were available for the study in only 393. The data was analysed by routine statistical methods and compared with that o f the general population and the weather parameters, obtained from the Department of Meteorology. i Results: The distribution o f births showed two peaks in M arch and August, where no such pattern was present in the general population. Considering the monthly rainfall, M arch and August are comparatively dry ibut the highest rainfall is observed in M ay and October. The rainfall peaks are exactly two months following birth peaks. The distribution o f socio-demographic factors was a reflection o f that o f the general population, except for sex showing male:female ratio o f 3:2 when the general population ratio is 1:1. 46.6% patients have abused substances and 42.3% had a positive family history o f mental illness. Conclusions: When compared to general population, the study sample showed a variation in tlie monthly birth pattern, with peaks in M arch and August and emphasized that seasonal changes following birth, is a possible risk to the later development o f schizophrenia in Sri Lanka.